The TiLOOP® male sling: did we forejudge - Hüsch, Tanja; Kretschmer, Alexander; Nyarangi-Dix, Joanne (Urologia internationalis, 2018)
Introduction: To evaluate the safety and efficacy of the TiLOOP® male sling (pfm medical, Cologne, Germany) used in the treatment for male stress urinary incontinence (SUI). Material and Methods: We retrospectively evaluated a total of 34 patients with a TiLOOP® male sling. Perioperative complication rates were assessed and validated questionnaires were prospectively evaluated to assess quality of life and satisfaction rate. Outcome and complication rates were analysed by using descriptive statistics. Correlation of continence outcome and risk factors was performed with the chi-square test. A p value below 0.05 was considered statistically significant. Results: The majority of patients (70.6%) were diagnosed with mild or moderate male SUI. During surgery, one instance (2.9%) of intraoperative urethral injury was observed. There were no immediate postoperative complications. The mean follow-up time was 44.6 months. An improvement of male SUI was reported by 61.9% of the patients and 38.1% reported no change according the Patient Global Impression of Improvement. The mean perineal pain score was 0.5 according to the international index of pain. Conclusions: The TiLOOP® is a safe treatment option for male SUI in our cohort with a low complication rate. However, the functional outcome of the TiLOOP® was inferior when compared to the outcome of the AdVance® male sling.
Published online: October 26, 2017
Gesehen am 05.11.2019